The occurrence and variation of Centaurea oxylepis (Wimm. & Grab.) Hayek in the Silesian Beskid - Nowak, Teresa (Biodiversity: Research and Conservation, 2006)
Results of preliminary studies on habitat requirements and morphological variation of Centaurea oxylepis are presented. The studies were carried out in the Silesian Beskid (West Carpathians). Fifteen populations were chosen for studies on morphological variation of the species. 28 traits of each specimen were analyzed using 1-Way ANOVA and G-test. The cluster analysis separated populations into two groups: one associated with southern slopes, other associated with northern and eastern slopes. 11 traits differentiated populations in statistically significant way. However, ranges of traits variation overlapped in majority of populations. The highest differentiation is evidenced in relation to: plant height, 1st-order ramifications number and the longest ramification length. Populations characterized by similar ranges of trait values were located on slopes similarly exposed. Probably, the morphological variation is caused only by habitat and climatic conditions.